Influence of implant surface modification on integration with bone tissue - Kutsevlyak, V. I.; Starikova, S. L.; Starikov, V. V.; Mamalis, A. G.; Lavrynenko, S. N.; Ramsden, Jeremy J. (Jointly by, Collegium Basilea (Institute of Advanced Study) and Association of Modern Scientific Investigation., 2008)
Problems connected with the improvement of medical implant fixation in bone tissue are addressed by the formation of a highly developed surface and by the activation of the implant surface with an electret coating. The realization of such surface modifications is expedient for implants manufactured from tantalum or niobium or finished by coatings made from these metals, as they are chemically more inert than titanium. The techniques have been tested on animals followed by histological and mechanical analysis.
Keywords: electret; electrostimulation; implant; niobium; osteointegration; oxide; porous coating; tantalum